Gut Microbiota of Pigs Metabolizes Extracts of Filipendula ulmaria and Orthosiphon aristatus–Herbal Remedies Used in Urinary Tract Disorders - Popowski, Dominik; Zentek, Jürgen; Piwowarski, Jakub P.; Granica, Sebastian (Planta Medica, 2021)
Urinary tract infections influence the mortality rate in pigs and are linked to extensive antibiotic usage in the farm industry. Filipendula ulmaria (L.) Maxim. and Orthosiphon aristatus (Blume) Miq. are widespread medicinal plants traditionally used to treat urinary tract disorders. As their preparations are orally administered, the metabolism of their constituents by gut microbiota before absorption should be considered. Until now, no experiments had been performed to describe the biotransformation of tthose plantsʼ extracts by animal gut microbiota. The study evaluates the influence of pig intestinal microbiota on the structure of active compounds in flowers of F. ulmaria and leaves of O. aristatus. The incubations of the extracts with piglet gut microbiota were performed in anaerobic conditions, and the samples of the batch culture were collected for 24 h. In F. ulmaria, the main metabolites were quercetin and kaempferol, which were products of the deglycosylation of flavonoids. After 24 h incubation of O. aristatus extract with the piglet gut microbiota, 2 main metabolites were observed. One, tentatively identified as 3-(3-dihydroxyphenyl)propionic acid, is likely the primary metabolite of the most abundant depsides and phenolic acids. The results confirm the formation of the compounds with anti-inflammatory and diuretic activity in the microbiota cultures, which might suggest F. ulmaria and O. aristatus for treating urinary tract disorders in piglets. Based on the similarities of human and pig gut microbiota, the pig model can help estimate the metabolic pathways of natural products in humans.
Keywords: Filipendula ulmaria; Orthosiphon aristatus; Rosaceae; Lamiaceae; microbiota; metabolism; swine, piglets; urinary tract